Olfactory dysfunction in type II diabetes: Therapeutic options and lessons learned from other etiologies – A scoping review - Sivakumar, Ram (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2022)
Olfactory dysfunction (OD) is highly prevalent amongst type 2 diabetes mellitus (DM2) patients and has many associated health risks. For example, OD can lead to poor nutrition, safety issues related to diminished hazard detection, and increased mortality rates. While limited research exists about therapeutics for DM2-associated OD, recovery of olfactory function is better studied in other pathologic states. The objectives of this scoping review are to synthesize the existing data on interventions for DM2-associated OD and present the evidence for therapies that have been utilized for non-DM2-associated causes of OD. Additionally, the potential therapeutic opportunities for patients with DM2 are explored.